2021
DOI: 10.1002/cam4.4216
|View full text |Cite
|
Sign up to set email alerts
|

ITGB4 as a novel serum diagnosis biomarker and potential therapeutic target for colorectal cancer

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…Additionally, serum ITGB4 was also identified as a novel prospective diagnostic biomarker for CRC by Jiang et al 34,35 Furthermore, ITGB4…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, serum ITGB4 was also identified as a novel prospective diagnostic biomarker for CRC by Jiang et al 34,35 Furthermore, ITGB4…”
Section: Discussionmentioning
confidence: 99%
“…ITGB4 has already been confirmed to have a high expression level and was associated with poor prognosis in colorectal cancer, implying ITGB4 could be used as a potential diagnostic and prognostic biomarker for CRC. Additionally, serum ITGB4 was also identified as a novel prospective diagnostic biomarker for CRC by Jiang et al 34,35 Furthermore, ITGB4 was also suggested to be upregulated in both LUAD and LUSC and has potential value in predicting lung cancer prognosis 36 . BRCA2 plays a significant role in cell physiology as a tumor suppressor that promotes DNA replication and DNA double‐strand break repair through homologous recombination 37 .…”
Section: Discussionmentioning
confidence: 99%
“…ITGB4 has been identi ed to be a novel promising serum diagnostic biomarker and a potential therapeutic target for CRC [30][31][32]. However, the association between ITGB4 and CAFs in CRC has not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…The PPyNW-modified biosensor showed significantly enhanced sensitivity, conductivity, and biocompatibility. In addition, serum angiopoietin, MST1/STK4, S100A9 TIMP1, ITGB4, Cyr61, and CXCL-8 in the blood have also been proven to have potential uses as biomarkers in the diagnosis and detection of colorectal cancer, and they could be employed in electrochemical sensor detection after further verification [ 166 , 167 , 168 , 169 , 170 ].…”
Section: Ppy-based Biosensors For Crc Biomarker Detectionmentioning
confidence: 99%